1984
DOI: 10.1161/01.cir.69.6.1146
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage and the products of fibrinogen digestion after intracoronary administration of streptokinase.

Abstract: Hemorrhage was prospectively identified in 26 of 116 consecutive patients (23%) who were receiving intracoronary streptokinase for occlusive coronary thrombi producing infarction. Bleeding was not influenced by the dose of streptokinase or the method of cardiac catheterization. Before treatment, prothrombin time and partial thromboplastin time were normal in both bleeders and nonbleeders. Fibrinogen levels measured by bioassay after streptokinase (mean + SEM) were 62 29 mg/dl in patients with major bleeding, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The short half-life of rt-PA and the lack of elaboration of functionally active fragments during the course of infusions of rt-PA probably contributed to the absence of prolonged adverse effects on the hemostatic system, in contrast to the case after infusion of conventional activators of the fibrinolytic system such as streptokinase." 17 Overall, in the group of patients given rt-PA, depletion of circulating fibrinogen was modest, depletion of circulating plasminogen was incomplete, and prolongation of the prothrombin time and/or protamine-corrected thrombin time was clinically insignificant.…”
Section: Discussionmentioning
confidence: 90%
“…The short half-life of rt-PA and the lack of elaboration of functionally active fragments during the course of infusions of rt-PA probably contributed to the absence of prolonged adverse effects on the hemostatic system, in contrast to the case after infusion of conventional activators of the fibrinolytic system such as streptokinase." 17 Overall, in the group of patients given rt-PA, depletion of circulating fibrinogen was modest, depletion of circulating plasminogen was incomplete, and prolongation of the prothrombin time and/or protamine-corrected thrombin time was clinically insignificant.…”
Section: Discussionmentioning
confidence: 90%
“…For this reason, the major impetus to the development of new thrombolytic agents has been the search for compounds with greater fibrin specificity. Older thrombolytic agents, such as streptokinase and urokinase, were known to be associated with significant bleeding complication rates [4,5], at least in part due to the systemic lytic state induced by the depletion of fibrinogen in the systemic circulation [6,7]. Early studies with the prototype fibrin-specific agent, tissue plasminogen activator (t-PA), suggested that although some systemic fibrinogen breakdown occurred, relative sparing of fibrinogen with a low bleeding complication rate was observed [8-lo].…”
mentioning
confidence: 99%
“…While thrombolysis alone may remove the thrombus burden in occluded grafts or coronary arteries, the anatomic precipitant may remain. In addition, even lower doses [22] or intracoronary adminjstratjon [23] may precipitate systemic fibrinogenolysis and may be contraindicated in the perioperative period. We regard thrombolysis as adjunctive therapy to direct angioplasty in this setting and use it with caution.…”
Section: Discussionmentioning
confidence: 99%